Re-examining the rare and the lost: a review of fossil Tortricidae (Lepidoptera) - Heikkilä, Maria; Brown, John W.; Baixeras, Joaquin; Mey, Wolfram; Kozlov, Mikhail V. (Zootaxa, 2018)
We re-evaluate eleven fossils that have previously been assigned to the family Tortricidae, describe one additional fossil, and assess whether observable morphological features warrant confident assignment of these specimens to this family. We provide an overview of the age and origin of the fossils and comment on their contribution towards understanding the phylogeny of the Lepidoptera. Our results show that only one specimen, Antiquatortia histuroides Brown & Baixeras gen. and sp. nov., shows a character considered synapomorphic for the family. Six other fossils (Electresia zalesskii Kusnezov, 1941; Tortricidrosis inclusa Skalski, 1973; Tortricites skalskii Kozlov, 1988; Tortricibaltia diakonoffi Skalski, 1992; Polyvena horatis Poinar and Brown, 1993 and a trace fossil purported to be larval feeding damage of Retinia resinella (Linnaeus, 1758)) exhibit a combination of homoplastic characters typical of tortricid moths or characteristic feeding damage. An unnamed species doubtfully assigned to Olethreutinae by Skalski (1992), Spatalistiforma submerga Skalski, 1992, Tortricites florissantanus (Cockerell, 1907), Tortricites destructus (Cockerell, 1916) and Tortricites sadilenkoi Kozlov, 1988 do not show enough character evidence to be convincingly placed in Tortricidae. Therefore, we transfer the three latter species from the collective group Tortricites Kozlov, 1988, defined as an assemblage of fossil leafrollers that cannot be placed with certainty in known genera, to Paleolepidopterites Kozlov, new collective group, defined as a group of fossil lepidopterans whose assignment to a certain family is currently impossible.